Impact of physiologically relevant temperatures on dermal absorption of active substances - an ex-vivo study in human skin - Kilo, S.; Wick, J.; Mini Vijayan, S.; Göen, T.; Horch, R.E.; Ludolph, I.; Drexler, H. (Toxicology in vitro, 2020)
Skin temperature plays a certain role in the dermal absorption of substances, but the extent and mechanisms of skin temperatures-induced modulation in ranges caused by physiological thermoregulation or environmental conditions are largely unknown. The influence of dermal temperature on the absorption of the model lipophilic compound (anisole) and the model hydrophilic compounds (1,4-dioxane, ethanol) through human skin was investigated at three dermal temperatures (25, 32 and 39 °C) in an ex-vivo diffusion cell model. The substances were applied to the skin and transdermal penetration was monitored. All substances showed temperature dependent variations in their penetration behavior (3 h: 25–39 °C: 202–275% increase in cumulative, transdermally penetrated amounts). The relative differences in absorption in relation to temperature were greatest within 45 min after exposure (25–39 °C: 347–653% rise in cumulated penetration), although absolute amounts absorbed were small (45 min vs. 3 h: 4.5–14.5%). Regardless of blood circulation, skin temperature significantly influences the amount and kinetics of dermal absorption. Substance-dependent, temperature-related changes of the lipid layer order or the porous pathway may facilitate penetration. The early-stage modulation of transdermal penetration indicates transappendageal absorption, which may be relevant for short-term exposures. For both, toxicological evaluation and perfusion cell studies, it is important to consider the thermal influence on absorption or to perform the latter at a standardized temperature (32±1 °C). •Regardless the effect on blood flow, skin temperature significantly influences absorption.•The impact of temperature on dermal absorption is substrate-specific.•The penetration pathways through skin are influenced differently by temperature.•The influence of the temperature varies over the time course of the absorption.